Welfare gains of joining a union for Latin America - Ardiles Decker, Fabrizio Leonardo (2023)
I present a set of scenarios that analyze the intention of a union for the case of Latin America countries by developing a calibrated DSGE model with heterogeneous union. The model accounts for both a monetary and a fiscal union that controls for real and financial frictions with the implementation of different monetary and macroprudential policy regimes.